2002
DOI: 10.1063/1.1446239
|View full text |Cite
|
Sign up to set email alerts
|

Growth of single-crystal CrN on MgO(001): Effects of low-energy ion-irradiation on surface morphological evolution and physical properties

Abstract: CrN layers, 0.5 m thick, were grown on MgO͑001͒ at T s ϭ570-775°C by ultrahigh vacuum magnetically unbalanced magnetron sputter deposition in pure N 2 discharges at 20 mTorr. Layers grown at T s р700°C are stoichiometric single crystals exhibiting cube-on-cube epitaxy: (001) CrN ͉͉(001) MgO with ͓100͔ CrN ͉͉͓100͔ MgO. At higher temperatures, N 2 desorption during deposition results in understoichiometric polycrystalline films with N fractions decreasing to 0.35, 0.28, and 0.07 with T s ϭ730, 760, and 775°C, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
56
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(66 citation statements)
references
References 55 publications
9
56
1
Order By: Relevance
“…In an initial study of deposition temperature, we observed that low temperature deposition at 550 • C or lower will lead to the formation of polycrystalline films with high electrical resistivity, while deposition temperatures higher than 700 • C typically results in predominant growth of Cr 2 N over cubic CrN consistent with earlier observations [49]. Thus, we limit the presentation of experiments below to the most important temper ature ranges between 600 • C and 700 • C.…”
Section: Initial Experimentsmentioning
confidence: 90%
“…In an initial study of deposition temperature, we observed that low temperature deposition at 550 • C or lower will lead to the formation of polycrystalline films with high electrical resistivity, while deposition temperatures higher than 700 • C typically results in predominant growth of Cr 2 N over cubic CrN consistent with earlier observations [49]. Thus, we limit the presentation of experiments below to the most important temper ature ranges between 600 • C and 700 • C.…”
Section: Initial Experimentsmentioning
confidence: 90%
“…26 The incident ion energy Ei and ion-to-metal flux ratio Ji/JMe are decisive parameters controlling nanostructural evolution during low temperature (< 500 o C; Ts/Tm < 0.3 for TiN) physical vapor deposition of transition-metal (TM) nitrides by conventional reactive DCMS. 17,25,27,28,29,30,31 The dominant ion species incident at the growth surface during DCMS with N2/Ar gas mixtures optimized to obtain stoichiometric films is typically Ar + , with N2 + and N + both contributing a few percent. 32, 33 The N2 + /N + ratio increases with increasing N2/Ar fraction, while in pure N2 discharges the dominant ion species is N2 + .…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Electronic transport studies report controversial results for CrN, including (i) values for the resistivity ρ at room temperature range over more than two orders of magnitudes, from 1.7×10 -3 to 3.5×10 -1 Ωcm, 3,[5][6][7][8][9][10] even when only considering the most reliable data for single crystal CrN layers; (ii) the temperature dependence of ρ shows metallic behavior with dρ/dT > 0 in some studies, 6,7,11 but an increase in ρ with decreasing temperature in other reports, 3,5,9,12 which has been attributed to the presence of a band gap 5 or carrier localization due to crystalline defects 13 or N-vacancies; 14 (iii) some studies report a discontinuity in ρ(T) at 260-280 K, 3,6,7,14 which is associated with a magnetic and structural phase transition from a paramagnetic NaCl structure at room temperature to a low-temperature antiferromagnetic orthorhombic P nma phase 11,15 with a 0.56-0.59% higher density, 11 and a 25% lower bulk modulus, 16 while other reports show no evidence for a phase transition in the ρ(T)-curves. 5,7,9 Electronic structure calculations suggest that magnetic stress relief couples magnetic ordering with the structural phase transition, 17 and that CrN exhibits a band gap if the Hubbard Coulomb interaction term is sufficiently large.…”
mentioning
confidence: 99%